PROSEDUR OPTIMASI SKENARIO WORKOVER UNTUK MEMPRODUKSI CADANGAN BEHIND PIPE PADA RESERVOIR DELTAIC - Tulus Bachtiar, Irfan
One of deltaic reservoir characteristics is the separation of the reservoir into unconnected thin layers. Characteristic difference of each reservoir layer causes inability to produce these layers together. This condition makes existing wells in the deltaic reservoir have remaining potential for behind pipe reserves in reservoir layers which have not been produced yet. This study describes optimization procedures of workover scenarios for producing behind pipe reserves in deltaic reservoir. Authors conducted a case study by designing workover scenarios of Field X as a guideline to build the general optimization procedure. The study is initiated by the observation of candidate wells and reservoir layers which are potentially produced. Authors identify characteristics of reservoir layers candidate, which are hydrocarbon type, reservoir pressure, and driving mechanism, as parameters in calculating reserves as well as determining workover scenarios. Analysis of workover scenario sensitivity is performed by producing reservoir layers separately and comminglely. Determination of the most optimum workover scenario is accomplished by assessing profitability index as the main economic parameter. Profitability index is further used for constructing workover priorities scale. The result of reservoir identification shows that some reservoirs own relatively similar characteristics thus enabling them to be produced comminglely. At the same well, commingled production strategy gives the highest economic value because it requires less time and lower workover costs. In Field X, there are 11 wells which are feasible to workover in 2016 with different priorities. The project will increase the production of Field X of 285.7 MBO and 1170.5 MMSCF, and will deliver NPV of MUS$ 2954 with a total investment of MUS$ 3850. Analysis carried through Field X case study is induced to design general optimization procedure of workover scenario in the form of flowchart. The flowchart is expected to be utilized as a guideline for the next workover optimization of Field X and other fields as well. The optimization procedure flowchart includes selection of wells and reservoir layers candidate, determination of production strategies, and determination of workover priority.